Analisis Potensi Daya Tarik Wisata Lanskap Budaya Jayengan Kampung Permata Surakarta - Hapsari, Pryscilla; Nurhayati; Kaswanto, Regan Leonardus (Jurnal Lanskap Indonesia, 2025)
Jayengan Kampung Permata (JKP), nestled within Surakarta City (Solo), is currently undergoing transformative development to emerge as a compelling thematic tourist destination, owing to its illustrious history steeped in trade, craftsmanship, gemology, and cultural heritage The aim of this research is to analyze the potential and assess selected areas of the JKP cultural landscape. After that, an analysis of the strategy for developing the cultural landscape to become a characteristic creative industrial tourism village was carried out using the SWOT method. The preparation stage begins with identifying the characteristics of the community in Jayengan Village based on literature study. This research method uses assessment parameters, which are taken from the Director General of Tourism Product Development using expert judgment. After that, calculate and analyze the classification of the area’s suitability level for the cultural landscape. The area feasibility results were then analyzed using the SWOT method to create a characteristic cultural landscape development strategy in JKP. The findings unearthed three exceptionally promising entities within Jayengan Kampung Permata: the Nashwa Workshop Jewellery, Poo Kiong Temple, and Ndalem Harjonegaran. These sites boast profound cultural significance and possess a magnetic allure for tourism. Nonetheless, they necessitate periodic maintenance and minor refurbishments to ensure their enduring sustainability. The amalgamation of distinct ownership frameworks and consistent upkeep procedures amplifies the inherent value of these attractions, rendering them robust and viable as premier tourist destinations.